Detection of Infectious Agents Causing Neonatal Calf Diarrhea on Two Large Dairy Farms in Yangxin County, Shandong Province, China - Wei, Xiaojuan; Wang, Weiwei; Dong, Zhen; Cheng, Fusheng; Zhou, Xuzheng; Li, Bing; Zhang, Jiyu (Frontiers in Veterinary Science, 2021)
Neonatal calf diarrhea (NCD) is one of the most serious health challenges facing the livestock industry and has caused substantial economic losses due to increased morbidity and mortality rates. The present study investigated the main infectious pathogens causing NCD among cattle in Yangxin County, China. Sixty-nine fecal samples were collected from diarrheic newborn cattle and tested for infectious agents, including bovine rotavirus, bovine coronavirus, Escherichia coli K99, Cryptosporidium parvum, and Giardia lamblia, that cause NCD, as determined by rapid kit analysis and polymerase chain reaction (PCR) amplification. The PCR results showed that the percentages of samples that were positive for C. parvum, bovine rotavirus A, bovine coronavirus, and G. lamblia were 44.93, 36.23, 17.39, and 13.04%, respectively. The rapid kit analysis results showed that the prevalence of C. parvum, rotavirus, coronavirus, and G. lamblia was 52.17, 31.88, 28.98, and 18.84%, respectively. No E. coli K99 was detected by either method. The total positivity of the samples, as determined by PCR and rapid kit analysis, was 80.00 and 81.16%, respectively. No significant difference between the two methods was observed. The results of this study may help to establish a foundation for future research investigating the epidemiology of NCD in cattle and may facilitate the implementation of measures to control NCD transmission to cattle in Yangxin County, Shandong Province, China.